RFID for the optimization of business processes - Hansen, Wolf-Rüdiger (John Wiley & Sons, 2008)
RFID for the Optimization of Business Processes is a descriptive introduction to the technology for business and technical managers, IT consulting experts and business process designers, as well as marketers of RFID technologies. The text will also be of great use to technical experts interested in business processes and also students studying the subject.